Neuroprotective effects of total phenolics from Hemerocallis citrina Baroni leaves through the PI3K/AKT pathway - Jia, Yanjun; Wang, Yanping; Wang, Zixia; Zhang, Zeyu; Zhang, Ju; Zhang, Jingjing; Sun, Ke; Hua, Yongchen; Chai, Guolin; Hu, Fangdi (Frontiers in Pharmacology, 2024)
Neurological injury, as a major pathogenic mechanism in depression, holds significant importance in the research and development of antidepressant drugs. Hemerocallis citrina Baroni (H. citrina), referred to as “Forgetting Sadness Grass”, has been confirmed to possess remarkable neuroprotective effects. Studies have identified that the total phenolics in Hemerocallis citrina Baroni leaves (HLTP) consist of flavonoids and phenolic acids and increasing experimental have substantiated the neuroprotective effects of them. Based on this, we propose that HLTP may possess neuroprotective properties. To confirm this hypothesis, we initially employed network pharmacology techniques to predict potential targets for the neuroprotective effects of HLTP based on the Swiss Target Prediction database. GO and KEGG analyses were conducted to predict potential pathways. Molecular docking experiments were then performed to analyze the binding abilities of the selected active components with the main targets. Furthermore, we validated the neuroprotective effects of HLTP and key targets selected through network pharmacology using a corticosterone-induced PC12 neuronal cell damage model. Network pharmacology research has identified that in the HLTP, Quercetin, Rutin, Apigenin, and Isoquercitrin are potential active components that may exert neuroprotective effects by modulating key targets such as AKT1, TNF, TP53, and CASP3 through crucial pathways including PI3K/AKT and apoptosis. Molecular docking revealed that 4-O-Caffeoylquinic acid, 5-O-Caffeoylshikimic acid, 4-p-Coumaroylquinic acid, and 5-O-Feruloylquinic acid exhibit low binding energies with key targets. HLTP can significantly increased the cell viability of cells induced by Corticosterone (Cort) in a dose-dependent manner by 9.50 %, 10.42 % and 21.25 %, respectively(P<0.01). Western blot analysis confirmed that HLTP significantly (P<0.01) increased the protein expression of PI3K and AKT by 15.24%, 30.44%, 41.03%, and 21.78%, 43.63%, 12.86%, respectively. In addition, through biochemical method, flow cytometry and WB analysis, we found that different concentrations of HLTP can all improve cell damage by reducing ROS, MDA, Ca2+, Cyt-C, Caspase-3, TNF-α and IL-1β, and increasing SOD, CAT, MMP, Bcl-2/Bax and IL-10. Through the above experiments, we verified that HLTP may exert neuroprotective effects by mediating the PI3K/AKT signaling pathway to counteract oxidative stress damage, improve mitochondrial dysfunction, and alleviate inflammatory injury.